1990
DOI: 10.1016/0014-5793(90)80727-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for measuring membrane conductance changes by a voltage‐sensitive optical probe

Abstract: This study presents a method whose principles enable using a voltage-sensitive optical probe, to quantitatively measure conductivity changes elicited in membrane vesicles and cells. The procedure is based on the fact that the amplitude of the transmembrane potential difference, established across a membrane by an external electric field, is decreased when membrane ~nducti~ty is increased upon incorporation of ionophores into the mcmbrane. The method was applied to osmotically swollen ~ylakoid membranes whose m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…We attribute the attenuation in the second EPL signal to a transient change in membrane conductance due to a reversible electric breakdown which takes place during and after the first pulse. To translate the relative attenuation of the EPL signal into a conductance change we used the same strategy whose principles enabled us to measure ionomycin-mediated conductivity changes (Rosemberg and Korenstein, 1990). The EPL signal is an explicit function of the electric field induced in the membrane rather than of membrane conductance itself.…”
Section: Study By Electrophotoluminescencementioning
confidence: 99%
“…We attribute the attenuation in the second EPL signal to a transient change in membrane conductance due to a reversible electric breakdown which takes place during and after the first pulse. To translate the relative attenuation of the EPL signal into a conductance change we used the same strategy whose principles enabled us to measure ionomycin-mediated conductivity changes (Rosemberg and Korenstein, 1990). The EPL signal is an explicit function of the electric field induced in the membrane rather than of membrane conductance itself.…”
Section: Study By Electrophotoluminescencementioning
confidence: 99%
“…The local membrane potential becomes 3 Vm = ~ E R cos0 and is built up with exponential kinetics with a time constant 3 7------~ pCm_/:~ where p is the specific resistance of the internal and external media and Cm the specific capacitance of the membrane (de Grooth et al 1980a). to investigate ionophore-mediated ion transfer across the membrane (Farkas et al 1982;Rosemberg and Korenstein 1990a), the equations are given by Farkas et al (1984a). For applications requiring separate treatment of the conductivities of internal and external media or a non-negligible conductivity of the membrane, e.g.…”
Section: Electric Field-induced Membrane Potentialmentioning
confidence: 99%
“…The study of EPL revealed some thermodynamic features of electron transport in PS I and PS H (van Gorkom et al, 1986;Vos andVan Gorkom, 1988, 1990) and established the electrophoretic and diffusional mobilities of PS I in the photosynthetic membrane (Brumfeld et al, 1989). Moreover, by using the EPL as an intrinsic voltage-sensitive optical probe, the electrical properties of the photosynthetic membrane were examined (Farkas et al, 1984a), electroporation characteristics of the photosynthetic membrane were explored (Farkas et al, 1984b;Korenstein et al, 1984;Rosemberg and Korenstein, 1990b) and ionophore-mediated ion ransport was studied (Farkas et al, 1982;Rosemberg and Korenstein, 1990a The present study employs the unique features of the EPL, which depend both on photosynthetic activity and on the conductance of the photosynthetic membrane, to elucidate stctural changes both in protein and the lipid-protein domains imposed by high electric fields.…”
Section: Introductionmentioning
confidence: 99%